Isolation and identification of angiogenesis-promoting components in Huanglian Jiedu decoction using live cell bio-specific extraction. (1st March 2023) - Liao, Fengyun; He, Dongmei; Liu, Cuiting; Vong, Chi Teng; Zhong, Zhangfeng; Wang, Yitao
Abstract: Ethnopharmacological relevance: Huanglian Jiedu Decoction (HLJDD) is a traditional heat-dissipating and detoxicating prescription used in Chinese medicine and has been extensively applied in the clinical treatment of ischemic stroke. Preliminary research confirmed that HLJDD exerts a neuroprotective effect on brain tissue injury caused by cerebral ischemia by promoting angiogenesis. However, the components of HLJDD responsible for its medicinal activity in ischemic injury remain unclear. Aim of the study: The aim of this study was to identify the active components of HLJDD that could promote angiogenesis and investigate its underlying mechanism, as well as Hypoxia-inducible factor-1α (HIF-1α)/Vascular endothelial growth factor (VEGF) signalings in human umbilical vein endothelial cells (HUVECs). Materials and methods: The specific binding components of HLJDD with HUVECs were isolated and identified through a combination of live cell biospecific extraction, solid-phase extraction, and ultra performance liquid chromatography (UPLC)-Orbitrap Fusion Tribrid mass spectrometry (MS). Their pharmacological activity against oxygen-glucose deprivation-reperfusion (OGD/R) injury and in vitro pro-angiogenesis was validated using Cell Counting Kit-8 (CCK-8) and tube formation analysis, respectively. Finally, we explored the effect of active ingredients on the expression levels of HIF-1α and VEGF using enzyme-linked immunosorbent assay. Molecular docking was used to predict the potential binding of six active components to phosphoinositide 3-kinase (PI3K), serine/threonine-specific protein kinase (AKT) and Von Hippel-Lindau (VHL) proteins, which are involved in the regulation of HIF-1α and are highly associated with angiogenesis. Results: A total of 13 HUVECs-specific HLJDD components were identified, and 10 of them were shown to protect against OGD/R injury. We were the first to demonstrate that two of these components have a protective role in OGD/R-induced HUVECs injury. Additionally, seven of these 10 components exhibited angiogenesis-promoting activity, and two of these components were shown, for the first time, to promote angiogenesis in HUVECs. These effects might occur through the HIF-1α/VEGF pathway. Molecular docking results showed that all six active ingredients could stably bind to PI3K and AKT proteins, suggesting that these two proteins may be potential targets for six active ingredients. Conclusions: The approach employed in this study effectively identified proangiogenic components in HLJDD that might act via PI3K/AKT/HIF-1α/VEGF pathways and other mechanisms involved in angiogenesis. In conclusion, this study was the first to demonstrate four compounds with new bioactivities and could also provide insight into the isolation and discovery of new bioactive compounds existing in Chinese medicine with potential clinical value. Graphical abstract: Image 1 Highlights: Cell-membrane chromatography was used to isolate 13 HUVEC-specific HLJDD components. Ten components protected against oxygen-glucose deprivation/reperfusion. Seven components demonstrated angiogenesis-promoting activity. Four compounds with new bioactivities were identified. Angiogenic HLJDD components upregulated HIF-1α and VEGF expression in HUVECs.